Pengaruh Motivasi Belajar Terhadap Kemampuan Pemahaman Konsep Matematis Siswa SMK - Putri Haryati Hasyim; Agung Prasetyo Abadi (Journal on Education, 2023)
Mathematics is a subject that many students do not like, it is found that students' learning motivation is low, because most vocational students are oriented towards work readiness only. Motivation is the encouragement of individuals or other people to do something. In addition, an important aspect of learning mathematics is the understanding of mathematical concepts within students. The purpose of this study was to find out whether there is an influence between learning motivation and the ability to understand mathematical concepts of SMK students. The approach used in this research is a quantitative approach with survey research methods. Data collection was carried out using questionnaires and tests. The population of this study were all students of class XI SMK PGRI 2 Karawang, the sample used was 22 students. The data analysis technique used is simple linear regression with the help of SPSS 25.0. Based on the calculations, the research results are indicated by the regression equation Y = 29.015 + 0.775 X indicating that if the motivation value is equal to (0) zero, the ability to understand students' mathematical concepts will decrease. The value of the coefficient X is 0.775, meaning that learning motivation has a positive effect on students' ability to understand mathematical concepts. the R2 value of 0.393 means that learning motivation has an effect on students' ability to understand mathematical concepts by 39.3% while the rest is influenced by variables or other factors.